Sternal metastasis from uterine leiomyosarcoma treated by near-total sternectomy and reconstruction with titanium sternal stabilization and fixation system - SOYSAL, ÖMER; Soysal, Omer; ZİYADE, SEDAT; ERGUN, Selma Sonmez; ERGÜN, SELMA; Ziyade, SEDAT; BÜYÜKPINARBAŞILI, NUR; Buyukpinarbasili, NUR; AKDEMİR, OSMAN CEMİL; Akdemir, OSMAN CEMİL (My University, 2015)
Uterine leiomyosarcomas are rare soft tissue neoplasms. Although they have a tendency to metastasize to distant organs, most commonly to the lung, liver and brain, rarely, sternal metastasis from a uterine leiomyosarcoma can occur. In this article, we report a 50-year-old female patient whose uterine leiomyosarcoma was treated with total abdominal hysterectomy and bilateral salphingo-oopherectomy, and who developed sternal metastasis five years later, which was completely resected and successfully repaired during the same session.